Cannabis: Drug of abuse and therapeutic agent, two sides of the same coin - Ana Canseco-Alba; Gabriela Rodríguez-Manzo (Permanyer, 2023)
The consumption of Cannabis sativa plant, known as marijuana in the Western world, for different purposes (therapeutic, intoxicating, and spiritual) due to its psychoactive effects, can be traced back to ancient times. Cannabis is the most used illicit drug worldwide; however, its legal status is changing rapidly. Cannabis regulation will allow a better understanding of its effects as a misused drug, including new challenges, such as the availability of highly potent Cannabis extracts. Furthermore, scientific research is making significant efforts to take advantage of the potential therapeutic uses of Cannabis active compounds. The science of Cannabis derivatives started with the identification of the phytocannabinoids -tetrahydrocannabinol (-THC) and cannabidiol (CBD), allowing the formal study of the complex set of effects triggered by Cannabis consumption and the deciphering of its pharmacology. -THC is recognized as the compound responsible for the psychoactive and intoxicating effects of Cannabis. Its study led to the discovery of the endocannabinoid system, a neuromodulatory system widespread in the human body. CBD does not induce intoxication and for that reason, it is the focus of the search for cannabinoid potential clinical applications. This review examines the current state of knowledge about contrasting perspectives on the effects of Cannabis, -THC, and CBD: their abuse liability and potential therapeutic use; two sides of the same coin.